Penerapan Line Balancing untuk Meningkatkan Proses Perakitan Control Panel di Line Service Part pada PT. Kawai Indonesia Plant 3 - Diki Aris Styawan; Wahyudin Wahyudin; Hamdani Hamdani (Fakultas Teknik, 2021)
The development of the industrial world is getting tighter, making each company must be able to overcome productivity to meet consumer demand. In increasing productivity, of course, you must make the production process efficient. One thing that can be done is to make line balancing. The purpose of this study is to identify and propose a track balance to make the production process more efficient. The data used in this research is in the form of the initial conditions of the work station and the type of work. The method used to identify the optimal trajectory balance is the Ranked Position Weight (RPW). From the results of data processing, it is known that the initial conditions of work stations on the control panel assembly are 5 stations and 16 types of work. From the results of the calculation of cycle time and the number of stations, the optimal number of stations is reduced to 3 work stations. After calculating using the Ranked Position Weight method, it is known that the 16 types of work can be grouped into 3 work stations. Then the balance delay is obtained after reducing the work station, which is 5.48% from the initial condition of 43.29%. Then the line efficiency after station reduction is 94.52% from the initial condition of 56.71%. Then the smoothing index after improvement was 0.983 from the initial condition of 6.128. From the results of the three indicators, it can be seen that the reduction of the station gives better results.